The corrosión inhibiting effect of polypyrrole films doped with p-tolune sulfonate benzene sulfonate or dodecyl sulfate anions, as coating on stainless en NCI aqueous solutions. - Romero Bonilla, Hugo (2014)
This article presents a study of the conditions for electro synthesis of polypyrrole (PPy) films on stainless steel, in the presence of the anions p toluene sulfonate (pTS), benzene sulfonate (BS) or dodecyl sulfate (DS). Cyclic voltammetry (CV) was used in the synthesis of the polypyrrole films on the stainless steel (SS). These polymeric films were characterized by IR and UV vis spectroscopy and their morphology and thickness were analyzed by scanning electron microscopy (SEM). Their performance as protective films against corrosive processes presented by the SS PPy pTS, SS PPy BS or SS PPy DS systems was evaluated in 0.1M NaCl aqueous solution. The study of the corrosion processes of the stainless steel/polymer systems was conducted through measurements of open circuit potential (EOCP ), polarization curves (PC) and electrochemical impedance spectroscopy (EIS). The results showed that the protective capacity of these polymeric systems on stainless steel, mainly with regard to pitting, depends on the nature of the anion dopant used during electro synthesis of the PPy film. The best performance was seen with the dopants pTS and BS.